Renovation as innovation: Repurposing human antibacterial peptide LL-37 for cancer therapy - Lu, Fatai; Zhu, Yingkang; Zhang, Guodong; Liu, Zunpeng (Frontiers in Pharmacology, 2022)
In many organisms, antimicrobial peptides (AMPs) display wide activities in innate host defense against microbial pathogens. Mammalian AMPs include the Cathelicidin and Defensin families. LL37 is the only one of the Cathelicidin family of host defence peptides expressed in humans. Since its discovery, it has become clear that they have pleiotropic effects. In addition to its antibacterial properties, many studies have shown that LL37 is also involved in a wide variety of biological activities, including tissue repair, inflammatory responses, hemotaxis and chemokine induction. Moreover, recent studies suggest that LL37 can the intricate and contradictory effects in promoting or inhibiting tumor growth. Indeed, an increasing amount of evidence suggests that human LL37 including its fragments and analogs shows anticancer effects in many kinds of cancer cell lines, although LL37 is also involved in cancer progression. Focusing on recent information, in this review, we explore and summarize how LL37 contributes to anticancer effect as well as discuss the strategies to enhance delivery of this peptide and selectivity for cancer cells.